Implementation of the Hidden Curriculum of Religious Moderation Education at State Islamic Senior High Schools in the Cirebon Region - Musahwi, Musahwi; Wahyuni, Yuni (Rumah Moderasi Beragama of Cyber Islamic University Syekh Nurjati Cirebon, 2024)
Through the Decision of the Ministry of Religious Affairs Number 184 of 2019 and the Decision of the Directorate General of Islamic Education Number 7272 of 2019, the implementation of religious moderation education from various levels of Islamic Education is carried out using a hidden curriculum strategy. The implementation of religious moderation education with hidden curriculum ideally outputs behavior based on moderate Islamic teachings. Since the institutional decision was implemented in 2019, there has been no in-depth study on the implementation of this hidden curriculum. Therefore, this research article will elaborate on the implementation of the hidden curriculum of religious moderation education and correct the alignment between students' understanding and actual behavior regarding religious moderation in State Islamic Senior High Schools (MAN) in the Districts and Cities of Cirebon. Some of the findings based on this research include: 1) school leaders and teachers have a discursive understanding of religious moderation, but not all understand the hidden curriculum in education; 2) religious moderation education is carried out based on each teacher's teaching method; 3) students' contextual understanding of religious moderation, in general, has been developed within the students themselves, but their social environment is homogeneous, making the actualization of factual values about religious moderation unverifiable; and 4) school leaders and teachers lack institutional initiative to develop religious moderation education within the schools they lead.